A bibliometric analysis of undergraduate theses from the School of Library and Information Studies from 2010-2014 an exploratory study - Balaquit, Jessica Patricia S.; Bugnosen, Marianne G.; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2015)
This study focused on the use of bibliometrics to perform qualitative research on the citations used in the undergraduate theses of UP SLIS from 2010-2014. The first step was to create a citation index that contains the article titles, authors, and journal titles used by the undergraduate students. Using existing tools such as BibExcel and VOSViewer, the researchers were able to convert the citation index from .xlsx file to .net file, producing bibliometric maps that reflect the relationships of the authors to each other and to the research tracks of UP SLIS.
The citation index created by the researchers allowed them to also perform quantitative analysis on the journal titles used by the undergraduate students based on their research tracks. The researchers were able to identify the titles of the journals used by the students and study their citation trends across the different tracks of UP SLIS. Bibliometrics is a field of study that has not been fully explored in UP SLIS. Through this study, the researchers were able to show how it can be used to reveal the research output of the college and its implications. The researchers also hope that with this study, other
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman
Keywords: Bibliographic citation; Bibliometrics